An online serious game for decision-making on food-water-energy nexus policy. (December 2022) - Ghodsvali, Maryam; Dane, Gamze; de Vries, Bauke
Highlights: A serious game for policy integration on food-water-energy nexus is developed. Methodologically, multi-objective optimization and game theory are combined. Players experiment with possible scenarios and examine the implications. Systemic thinking and possibilities for policy integration are discussed. The need for stakeholder engagement to effectively integrate policies is stressed. Abstract: Food-water-energy nexus is a complex problem characterized by multiple alternatives, conflicting objectives, and multiple uncertainties about key drivers like climate change, urbanization, and population growth. Serious games are becoming a popular means to support decision-makers who are responsible for the management of urban food, water, and energy systems. However, the effectiveness of these games in improving decision-making and the quality of their outcomes remains low. Therefore, in this paper, we developed a serious game, namely S.N.O.G., which offers a safe decision-making environment where impacts of decisions may be tested and rated. Methodologically, S.N.O.G. is developed based on a combination of multi-objective optimization programing and game theory. Spatial representation, forecast, automatic feedback, ease of information communication, transparency, ease of modification add to the competence of S.N.O.G.'s application into effective decision-making for food-water-energy nexus. The game was tested in a smart-eco district in the Netherlands for which balanced food production, water management and energy generation is the goal. By using an activity theory-based model, we evaluated and mapped how S.N.O.G. contributes to the advancement in decision-making. Our research shows the game helped participants identify and indicate key drivers of integrated resource management, and how the game can strengthen the learning policy outcomes.